2010
DOI: 10.1007/s10534-010-9399-9
|View full text |Cite
|
Sign up to set email alerts
|

Iron acquisition with the natural siderophore enantiomers pyochelin and enantio-pyochelin in Pseudomonas species

Abstract: The bacterial siderophore pyochelin is composed of salicylate and two cysteine-derived heterocycles, the second of which is modified by reduction and N-methylation during biosynthesis. In Pseudomonas aeruginosa, the first cysteine residue is converted to its D-isoform during thiazoline ring formation, whereas the second cysteine remains in its L-configuration. Stereochemistry is opposite in the Pseudomonas fluorescens siderophore enantio-pyochelin, in which the first ring originates from L-cysteine and the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
130
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(131 citation statements)
references
References 61 publications
1
130
0
Order By: Relevance
“…It is important to note here that both siderophores are synthetized through non-ribosomal peptide synthesis [11,12]. This means that an entire machinery of enzymes first needs to be produced, and only then are the siderophores assembled from amino acids and other chemical compounds.…”
Section: (E) Fitness Consequences Of Siderophore Switchingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note here that both siderophores are synthetized through non-ribosomal peptide synthesis [11,12]. This means that an entire machinery of enzymes first needs to be produced, and only then are the siderophores assembled from amino acids and other chemical compounds.…”
Section: (E) Fitness Consequences Of Siderophore Switchingmentioning
confidence: 99%
“…) [12] than pyoverdine (K f ¼ 10 24 M 21 ) [11] and is less important for virulence [16]. Despite its apparent inferiority to pyoverdine under typical conditions, it has been suggested that under less stringent iron limitation, pyochelin might prove most useful [4].…”
mentioning
confidence: 99%
“…Iron uptake with Pch and its regulation have been studied in detail and reviewed by Youard et al (2011). The genes responsible for Pch biosynthesis are organized in two operons, pchDCBA and pchEFGHI, which are located next to the pchR regulatory gene and to the ferriPch (iron-loaded form of Pch) transport operon fptABCX (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The genes for EPch biosynthesis in P. fluorescens are organized in a single transcriptional unit, pchDHIEFKCBA, which is clustered with pchR and a putative ferriEPch transport operon, fetABCDEF ( Fig. 1b; Youard et al, 2011). By analogy with P. aeruginosa, the PchR protein of P. fluorescens, together with EPch, activates expression of the pchDHIEFKCBA operon ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation